Answer:
68
Step-by-step explanation:
The expression is given as:
4( 3+ 7y) + 6(2 - y)
It is known that y is equal to 2. Therefore, substitute 2 in for y.
4(3+7(2))+6(2-2)
Now, solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition, Subtraction
Solve inside of the parentheses first.
4(3+7(2))+6(2-2)
4(3+14)+6(0)
4(17)+6(0)
Multiply
68+0
Add
68
Answer:
343 yd
Step-by-step explanation:
Answer:
If you aren't looking for the quadratic solving method then comment it down below and tell me what you're looking for
QUADRATIC EQUATION
x²- 4x = 6
(x - 2)²- 4 = 6
(x - 2)² = 10
x - 2 = ±10
x = ±10+2
x = -8, 12
First write it in vertex form :-
y= a(x - 2)^2 + 3 where a is some constant.
We can find the value of a by substituting the point (0.0) into the equation:-
0 = a((-2)^2 + 3
4a = -3
a = -3/4
so our equation becomes y = (-3/4)(x - 2)^2 + 3